Working With Violent Youth: Application of the Transtheoretical Model of Change - Willoughby, Todd; Perry, Garry P. (Canadian Journal of Counselling and Psychotherapy, 2007)
Violent behaviour by adolescents has become a growing concern in Canada. Many authors highlight the need to provide specialised services to this population. However, violent youth present multiple challenges to professionals. This article highlights how the Transtheoretical Model of Change (TMC) can be utilized to guide treatment interventions with adolescents who engage in violent behaviour. Section one reviews treatment issues related to providing services to violent adolescents. Section two describes the use of the TMC with adolescents from different cultural backgrounds who change their high-risk behaviours. Section three overviews the utilization of the TMC in dealing with violence. Section four provides suggestions regarding the application of the TMC with violent adolescents. The paper concludes with a discussion of the applicability of TMC across a range of clinical and counselling settings. The positive aspects of TMC, including the provision of cost-effective services to clients and working with reluctant clients, are highlighted.